The profile of contractual issues associated with subcontracts in Malaysian construction industry [electronic resource] - Mohd. Ehyauddin Ahmad Zaki, 1986- (2013)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - UniversitiTeknologi Malaysia, 2013